2023
DOI: 10.3390/gels9030233
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sage (Salvia sclarea) Essential Oil on the Physiochemical and Antioxidant Properties of Sodium Alginate and Casein-Based Composite Edible Films

Abstract: The aim of this study was to examine the effect of Sage (Salvia sclarea) essential oil (SEO) on the physiochemical and antioxidant properties of sodium alginate (SA) and casein (CA) based films. Thermal, mechanical, optical, structural, chemical, crystalline, and barrier properties were examined using TGA, texture analyzer, colorimeter, SEM, FTIR, and XRD. Chemical compounds of the SEO were identified via GC–MS, the most important of which were linalyl acetate (43.32%) and linalool (28.51%). The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The film incorporated with CEO showed optimal potential (96.25%), followed by the film with TEO. These findings are in line with the results obtained by Lin et al (2020), Pires et al (2013), and Bhatia et al (2023), who likewise concluded that the antioxidant activity of edible films generally increases with the incorporation of EOs. We also observed a minor inhibition of DPPH free radicals in the control film.…”
Section: Resultssupporting
confidence: 92%
“…The film incorporated with CEO showed optimal potential (96.25%), followed by the film with TEO. These findings are in line with the results obtained by Lin et al (2020), Pires et al (2013), and Bhatia et al (2023), who likewise concluded that the antioxidant activity of edible films generally increases with the incorporation of EOs. We also observed a minor inhibition of DPPH free radicals in the control film.…”
Section: Resultssupporting
confidence: 92%
“…Edible films were fabricated using the casting technique outlined in our prior investigation. 8 A filmogenic solution containing carrageenan was prepared by combining 2% (w/v) carrageenan with 100 mL of distilled water. Subsequently, the mixture was subjected to agitation at 800 rpm, utilizing a magnetic stirrer (Daihan Scientific, Seoul, Korea), for a duration of 20 min, maintaining a temperature of 60 °C.…”
Section: Development Of Filmsmentioning
confidence: 99%
“…Mechanical Attributes. The mechanical characteristics of the film samples were evaluated following the procedure outlined by Bhatia et al 8 The experimental approach followed the ASTM D882 standard method guidelines using a texture analysis (TA. XT plus, Stable Micro Systems, England) with a 5 kg load cell.…”
Section: Development Of Filmsmentioning
confidence: 99%
“…Neutralization of acid casein with sodium hydroxide leads to the formation of sodium caseinate, which is water-soluble. Casein has been studied for use in a number of applications, including controlled release systems, textile fibers, flame-retardant compounds, and edible films . In the biomaterials area, its mixture with polycaprolactone (PCL) and gelatin for the fabrication of electrospun webs and application in cartilage tissue engineering has been considered .…”
Section: Introductionmentioning
confidence: 99%